American tegumentary leishmaniasis - a case of therapeutic challenge - Daíne Vargas Couto; Gunter Hans Filho; Marcelo Zanolli Medeiros; Carolina Faria Santos Vicari; Aline Blanco Barbosa; Luiz Carlos Takita (Sociedade Brasileira de Dermatologia, 2014)
American Tegumentary Leishmaniasis (ATL) is a chronic, non-contagious, infectious disease affecting millions of people worldwide. The timely and proper treatment is of great importance to prevent the disease from progressing to destructive and severe forms. Treatment for ATL recommended by the Brazilian Ministry of Health is similar for the whole country, regardless of the species of Leishmania. It is known that the response to treatment may vary with the strain of the parasite, the immune status of the patient and clinical form. We report the case of a healthy patient, coming from Manaus, Amazonas state, Brazil, who presented resistance to treatment with N-methyl-glutamine and liposomal amphotericin B, only being healed after using pentamidine.